2012
DOI: 10.1039/c2cc17611d
|View full text |Cite
|
Sign up to set email alerts
|

Vortex fluidic exfoliation of graphite and boron nitride

Abstract: Graphite is exfoliated into graphene by shearing vortex fluidic films of N-methyl-pyrrolidone (NMP), as a controlled process for preparing oxide free graphene, and for exfoliating the corresponding boron nitride sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
277
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(284 citation statements)
references
References 20 publications
5
277
0
2
Order By: Relevance
“…However, a recent paper has shown that graphite can be exfoliated to give graphene by generating shear in a very thin liquid layer in a rapidly rotating tube. 22 However, this method gives very small quantities of graphene and is inherently un-scalable. Here we demonstrate a method for shear-exfoliation of graphite to give graphene that is many times more efficient than sonication but which can be scaled-up to an industrial level.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent paper has shown that graphite can be exfoliated to give graphene by generating shear in a very thin liquid layer in a rapidly rotating tube. 22 However, this method gives very small quantities of graphene and is inherently un-scalable. Here we demonstrate a method for shear-exfoliation of graphite to give graphene that is many times more efficient than sonication but which can be scaled-up to an industrial level.…”
Section: Main Textmentioning
confidence: 99%
“…14 We can understand these processes by modelling exfoliation as shear-induced intermonolayer sliding in a solvent. 14,22 This predicts a minimum shear rate given by: Equation 1 can be rewritten to express the minimum flake size that can be produced by shear exfoliation at a given  . 14 Then, the average flake size, L , is approximately the mean of this value and the maximum flake size retained after centrifugation, LCF.…”
Section: Main Textmentioning
confidence: 99%
“…More recently it has been demonstrated that liquid exfoliation can be achieved by exposing graphite to high shear rates 34 using either rotor-stator high shear mixers 35,36 or simple kitchen blenders. 37,38 This gives graphene nanosheets of similar size and quality to those produced using sonication.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date only preliminary results have been demonstrated for the scale-up of liquid phase exfoliation of inorganic layered materials such as MoS2, WS2 and BN. 34,35 To facilitate scaleup, it will be important to demonstrate an effective large-scale shear exfoliation of such materials with rotating blade mixers and to identify optimised processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the shear force cannot be estimated accurately because of the complexity of the velocity distribution in turbulence ow, but the exfoliation capability of the uidic shear force has been proved by the graphene exfoliation experiment done by Chen et al using a vortex uidic device. 36 Along with the exfoliation process, perforation takes place simultaneously. As shown in Fig.…”
mentioning
confidence: 99%